Forced Migration and Global Processes: A View from Forced Migration Studies - Crepeau, Francois; Nakache, Delphine; Collyer, Michael; Goetz, Nathaniel H.; Hansen, Art (Lexington Books, 2006)
Migration is at the center of much of the discussion on globalization. Migrants move across borders and thus defy state-centered traditions. Migration is often caused or influenced by aspects of global change: the transformation of the world economy with the expansion of free trade, the modification of the world balance of power and the challenge of global insecurity, the emergence of the global environment as an important political issue, and the redefinition of the role of communities in shaping identities when faced with networks of migrants and diasporas. Forced Migration and Global Processes considers the crossroads of forced migration with three global trends: development, human rights, and security. This expert collection studies these complex interactions and aims to help determine what solutions may alleviate most of the human suffering involved in forced migrations.